Usual Interstitial Pneumonia Associated With Crystalline Silica Exposure in Pneumoconiosis: A Retrospective Cohort Study. Issue 12 (December 2021) - Kang, WonYang; Kim, Daeho; Kim, Mi-Yeon; Kim, Boowook; Shin, Jungah; Kim, Eun Young; Choi, Sungwon; Cha, Wonseok; Choi, Byung-Soon
Abstract : Objective: We aimed to identify a relation between the level of silica exposure and the associated increase in the risk of radiologic usual interstitial pneumonia (UIP) pattern. Methods: We selected data of 796 individuals with pneumoconiosis who had undergone a chest computed tomography (CT). We estimated the silica exposure by comparing their occupational history with the data silica dust exposure. Results: Individuals employed as stonemasons demonstrated a 2.30-fold increase in the risk of developing UIP than coal mine workers (odds ratio [OR], 2.30; 95% confidence interval [CI], 1.04 to 5.07). The high silica exposure group was associated with a 2.23-fold increase in the risk of developing UIP than the low silica exposure group (OR, 2.23; 95% CI, 1.07 to 4.69). Conclusions: This study suggests that silica exposure is associated with an increased risk of developing UIP pattern, highlighting a dose–response relationship.